Pre-Service Teachers’ Attitudes towards Learning and Teaching English to Young Learners - Bratož, Silva (Revija za elementarno izobraževanje, 2015)
Considerable attention has recently been invested into researching the influence of affective variables, such as attitudes and motivation on foreign language learning and teaching. The topic is timely and relevant especially at the time when English is being introduced as an obligatory subject in the first cycle of primary school in Slovenia. Two key issues are addressed: attitudes towards learning and teaching English as a foreign language and the profile of the young learners’ language teacher. The article presents the results of a small-scale research conducted with a group of primary education students on their attitudes towards learning and teaching English. The results suggest that trainee teachers have moderately positive attitudes towards learning English but diverse attitudes towards teaching a foreign language.